Typological Classification of German and Ukrainian Paralinguistic Phraseological Units (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with paralinguistic phraseological units of German and Ukrainian as specific language nominations for designation of the nonverbal human behavior. An attempt to classify the investigated units according to the stated criteria is presented.
Keywords: typological aspekt; paralanguage; paralinguistic phraseological units; kinegram; nonverbal behaviour; verbalisation